Croton nagaoi, a new species of Euphorbiaceae from southern Laos - Tagane, Shuichiro; Souvannakhoummane, Keooudone; Souldeth, Phetlasy (Phytotaxa, 2022)
Croton nagaoi (Euphorbiaceae) is described based on a specimen collected from the basin of the Bolaven Plateau, southern Laos. It is most similar to Croton thorelii Gagnep. of Laos, Cambodia, Thailand and Vietnam in size and shape of lamina, short petioles less than 1 cm long, and basal glands lateral on the abaxial midrib base, but different in having densely stellate hairy lower leaf surface (vs. very sparsely pubescent and glabrescent in C. thorelii), smaller sepals and petals of staminate flowers (sepals and petals ca. 2.2 mm long vs. 3 mm long and 2.5 mm long, respectively), and the presence of petals in pistillate flowers (vs. absent). Morphological descriptions, photographs, vernacular name, and preliminary conservation status are provided for C. nagaoi.